EFFECTIVENESS OF SEROLOGICAL TESTS FOR DIAGNOSTICS OF BOVINE EPHEMERAL FEVER - Ye. A. Konstantinova; S. K. Starov; A. V. Konstantinov; V. I. Diev; A. K. Karaulov (Ветеринария сегодня)
Review of publications devoted to spread of bovine ephemeral fever (BEF) in the world is presented; epizootic aspect of this problem is highlighted. The disease is not registered in Americas, Island, New Zealand and Europe. African continent, Australia and Asian countries including those neighboring the Russian Federation are considered BEF infected, that is why there is a risk of BEF introduction into our country. Serological tests for BEFV antibodies in the Russian Federation were performed for the first time. In total 13,911 samples, collected in 2008-2010 on farms in 26 regions of the Russian Federation were tested. Testing of cattle sera using prolonged complement fixation test revealed 333 BEFV seropositive samples, submitted from 9 regions in 2008, percentage by region was 2.6-25.9%, average percentage was 9.7% out of the total number of samples tested during the abovementioned period. Sera specific activity was determined when they were used non-diluted or diluted at 1:10-1:20. Sera with positive reactions in prolonged CFT showed specific activity in ELISA at 1:10-1:1,280 dilutions, but if diffusion precipitation test with non-diluted sera was used antibodies were detected only in few samples due to insufficient sensitivity. Test results proved the possibility of serological monitoring using prolonged CFT and ELISA. Due to insufficient sensitivity of diffusion precipitation test, its use for this purpose is not feasible.